Supplementary materials for PhD thesis “The Aeolian Roof: a building integrated wind and solar energy system in order to supply the electricity needs of a building” - Antonio Aguiló-Rullán (20346133) (2024)
This dataset comprises the files contained on a CD-ROM which was attached to the thesis when it was submitted in 2007. It was uploaded to ORDO in 2024 for preservation purposes. For more information, please refer to the thesis “The Aeolian Roof: a building integrated wind and solar energy system in order to supply the electricity needs of a building” via ORO. Abstract This thesis has researched an innovative way of providing ‘zero carbon dioxide emitting electricity’ by the use of a patented novel wind or wind and solar building integrated energy system, the Aeolian Roof. The Aeolian Roof conceived and patented by Dr Derek Taylor, is specifically intended to act as a wind power concentrator, increasing the amount of wind resource available on the top of the building for wind energy exploitation. In order to achieve that, the Aeolian Roof uses a special fairing or wing-like 'planar concentrator' known as a SolAirfoilTM, which, in the particular arrangement examined in this thesis is attached and aligned to the upper region of the roof of a building. The theoretical modelling of the Aeolian Roof has been undertaken with the aid of steady-state two dimensional Computational Fluid Dynamics (CFD) simulations. CFD results led to the construction of the first Aeolian Roof prototype on a dual pitch low-rise building located on an open country terrain. The experimental part of this work has shown that the Aeolian Roof concept works as a means of enhancing the power generated by a building-mounted wind turbine. For the Aeolian Roof configuration tested, it is possible to increase the wind power generated by a wind turbine in the Aeolian Roof by up to 60%. Means of achieving further enhancement have been identified as a result of this work and further testing is currently taking place. The combination of hourly weather data and the experimental results have shown that for a site with an annual mean wind speed of 4.6 m/s on an exposed terrain the annual electricity produced with an Aeolian Roof should be capable of exceeding that generated over a year by the same wind turbine mounted on a mast - but able to yaw - by 12%. In terms of providing a value for the cost of the electricity generated with the Aeolian Roof, the analysis undertaken in this thesis has shown that for discount rates between 3.5% and 7.5% the cost of the electricity generated with the Mark 1 Aeolian Roof could be between 12 and 16 p/kWh respectively.